Guests Experience and Satisfaction on Operations in Yap Hotels: An Enhancement to Smart Technology Adaption - Punongbayan, Ma. May A.; Bucal, Remedios J. (International Journal of Research in Interdisciplinary Studies, 2025)
This research explores how guest experience and satisfaction influences operational practices with respect to Yap Hotels, focusing on the impact of smart technology adaptation on service quality improvement and operational efficiency. The study investigates the current operational processes, consolidates development proposals, and evaluates guest reviews to identify how automation, artificial intelligence (AI), and devices connected through the Internet of Things (IoT) can streamline hotel procedures and improve the experience. The research answers the question of how technological innovations can fulfill guests’ expectations of tailored service, effortless interaction, and streamlined processes through the use of guest surveys, staff interviews, and operational audits. The results meaningfully analyze the advantages and disadvantages of incorporating smart technologies and provide practical guidance for Yap Hotels where innovative strategies can be used to strengthen hotel competitiveness and guest satisfaction. This research enables Yap Hotels to know how to strategically utilize smart technology in enhancing operational efficiency and guest satisfaction.